2009
DOI: 10.1038/bmt.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients developing GVHD after DLI given to treat CML relapse: a study by the chronic leukemia working party of the EBMT

Abstract: We studied GVHD after donor lymphocyte infusion (DLI) in 328 patients with relapsed CML between 1991 and 2004 . A total of 122 patients (38%) developed some form of GVHD. We analyzed GVHD by clinical presentation (acute or chronic GVHD) and onset time after the first DLI (early (p45 days) or late (445 days)). There was a significant overlap between onset time and clinical presentation. Some form of GVHD occurred at a median of 104 days, acute GVHD at 45 days and chronic GVHD at 181 days after DLI. The clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
2
48
1
Order By: Relevance
“…103 However, discrepancies exist among different studies. Chalendon et al 9 showed that GVHD was more frequent in patients with a higher cell dose for 410 7 CD3+ cells/kg than for o10 7 CD3+ cells/kg (47% vs 34%, Po 0.01) after DLI in patients with relapsed CML after allo-HSCT. Similarly, another study also showed that the dose of DLI (⩾1 × 10 7 ) was a predictive factor of acute GVHD.…”
Section: Gvhd and Gvl After DLImentioning
confidence: 99%
See 1 more Smart Citation
“…103 However, discrepancies exist among different studies. Chalendon et al 9 showed that GVHD was more frequent in patients with a higher cell dose for 410 7 CD3+ cells/kg than for o10 7 CD3+ cells/kg (47% vs 34%, Po 0.01) after DLI in patients with relapsed CML after allo-HSCT. Similarly, another study also showed that the dose of DLI (⩾1 × 10 7 ) was a predictive factor of acute GVHD.…”
Section: Gvhd and Gvl After DLImentioning
confidence: 99%
“…As a prophylactic or therapeutic regimen, DLI has been widely employed to boost the graft-vs-tumor (GVT) or GVL effects. 3,6,7 Clinical data have shown that DLI is most effective for CML [7][8][9][10] and the response rate is 70-80% for hematological or cytogenetic relapse, 9 whereas the benefit of DLI for relapsed acute leukemia is often limited, 11 mainly because of the rapid growth of leukemic cell burden, poor response to the GVL reaction 9 and the development of GVHD 12 and aplasia. 8 To overcome these limitations, researchers have attempted to modify the DLI strategies depending on different clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of DLI in some patients who relapse after AHSCT can result in disease remission, DLI may increase the risk of acute GVHD (aGVHD). [1][2][3][4][5] These findings have led to an interest in the kinetics of post-transplant lymphocyte recovery as a surrogate for effective immune reconstitution and as a predictor of transplant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that, although there is no clear time point that we could recommend, DLI could be postponed despite molecular evidence of relapse and be given no later than in hematologic chronic phase relapse, in line with previous reports that showed that DLI given at least two years after allogeneic HSCT had a lower risk of leading to GvHD. 14,19 This issue now becomes even more complicated in the era of TKI. Patients could receive TKI for posttransplant relapse 20,21 or DLI or both.…”
Section: Discussionmentioning
confidence: 99%